Inhibition of glucuronomannan hexamer on the proliferation of lung cancer through binding with immunoglobulin G. (15th November 2020) - Jin, Weihua; He, Xinyue; Zhu, Jiachen; Fang, Qiufu; Wei, Bin; Sun, Jiadong; Zhang, Wenjing; Zhang, Zhongshan; Zhang, Fuming; Linhardt, Robert J.; Wang, Hong; Zhong, Weihong
Highlights: Glucuronomannan-hexamer showed strong interaction with immunoglobulin G. The structure-activity relationship between degree of polymerization and its anti-lung cancer activity was investigated. Glucuronomannan-hexamer exhibited anti-lung cancer activity through immunomodulatory effects. Abstract: The anti-lung cancer activity of oligosaccharides derived from glucuronomannan was investigated. The inhibition of A549 cell proliferation by glucuronomannan (Gn) and its oligomers (dimer (G2), tetramer (G4) and hexamer (G6)) were concentration dependent. In vivo activities on the A549-derived tumor xenografts showed the tumor inhibition of G2, G4 and G6 were 17 %, 40 % and 46 %, respectively. Organ coefficients in nude mice showed an increase in the kidney with G4, the brain with G6, and the spleen with G6. An advanced tandem mass tag labeled proteomics approach was performed. A significant differential expression was found in 59 out of the 4371 proteins, which involved the immune system. Surface plasmon resonance (SPR) studies revealed G6 was strongly bound to immunoglobulin G. This suggests that glucuronomannan hexamer inhibits the proliferation of lung cancer through its binding to immunoglobulin.